SACAR LA VOZ - INTERNATIONAL PERSPECTIVES ON CHILDREN'S VIDEO GAME DESIGN - Croasdale, Alison; Guzman, Pilar De La Maza (Brazilian Creative Industries Journal, 2026)
This paper discusses an international, children-focused game design research project, occurring between Santiago, Chile, and London, UK. This research took place in schools in Santiago and London, and involved students between 11-15 years old creating microgames (mostly using the free, browser-based software ‘Bitsy’) that reflected both the existing games the participants were already fans of, and the political events from the world around them that they found most important in their lives. The purpose of this project was to explore the potential of videogame making for allowing young people to articulate their opinions on the world around them, in a media form that was directly of interest to them and their usual cultural practices. For the students themselves, this experience was also designed to be a promotion of critical digital literacy skills and to act as a way of allowing them to interrogate the ‘news’ shaping their lived experience, through creativity and play.